Cyrtodactylus dati, a new forest dwelling Bent-toed Gecko (Squamata: Gekkonidae) from southern Vietnam - van Tri, Ngo (Zootaxa, 2013)
A new species of Bent-toed Gecko, Cyrtodactylus dati sp. nov. is described from the secondary evergreen forests of Bu Dop District, Binh Phuoc Province, Vietnam. It differs from all other species of Indochinese and Thai-Malay Cyrtodacty-lus by having a maximum SVL of 70.1 mm (n=6); no distinct dark blotches on the head in adults; no continuous nuchal loop; a blotched dorsal pattern; 17–19 interorbital scales across the frontal bone; 23–26 scales in a straight line between eye and nostril; 42–48 rows of ventral scales between ventrolateral folds; 20–22 irregular, longitudinal rows of keeled tu-bercles at midbody between the ventrolateral folds; a series of five or six precloacal pores medially interrupted by one poreless scale in males; three or four femoral pores on each thigh in males; 4–7 enlarged scales beneath thighs; 12–13 subdigital lamellae on first toe; 18–19 subdigital lamellae on fourth toe; and small subcaudal scales.